The Effects of HLA-G Gene Polymorphism and sHLA-G Level in Women with Threatened Abortion - Ahmed H. Merdas; Mayada N. Iqbal; Nisreen Sherif Alyasiri (Journal of Techniques, 2022)
The most frequent first-trimester problem is a miscarriage, which affects 20% of pregnancies. In approximately 20-25 percent of confirmed pregnancies, threatened miscarriage is indeed a risk factor that may develop or resolve. This study aimed to assess the impact of certain HLA-G gene SNPs and sHLA-G serum levels to determine whether they play a role in threatening abortions. This study included 90 subjects who were separated into three groups: 30 patients (threatened abortion patients), and 60 controls (30 healthy pregnant women and 30 healthy non-pregnant women). All of the study groups were between the ages of 20 and 35 years old. The mean sHLA-G level in pregnant women's sera was found to be 430.38 Pg/ml, compared to 307.98 Pg/ml in the threatened abortion group and 192.11 Pg/ml in non-pregnant women (P= 0.001). The rs2249863 T/C/G was a statistically significant difference between the T allele and the G allele, with an odds ratio of 1.720 (p-value = 0.038). In conclusion, serum sHLA-G levels in threatened abortion patients' sera are significantly lower than in normal pregnant women. Allele frequencies of HLA-G gene snps were non-significant changes between TA patients and controls, except rs2249863 T/C/G.